DECORATIVE LAYERS ON SILICON BRONZES (Metallurgy and Foundry Engineering, 2011)
Decorative coatings artificially obtained on the surfaces of copper castings, commonly called artificial patinas in opposition to natural patinas, allow for adjusting the colour, the gloss, and the colour intensity of a casting to the customer demands. A decorative coating is a part of the artistic casting and the key element to the impression exerted by a sculpture. The colour, the type, and quality of a decorative coating depend on the author's intention, so that an artistic foundry should deal successfully with a variety of demands. Beside exerting the strictly artistic impression, patinas have one more goal to achieve - it is the corrosion protection. Natural patinas arising nowadays are characterised by Iow quality, irregular thickness, numerous cracks, and the dull taupe-brown colour. Therefore there exists need of generating decorative coatings in a controlled way. The present work is aimed to determine the influence of mechanical abrasive working applied to the surfaces of BK331 silicon bronze castings on the quality and durability of the obtained decorative coating for given recipes for patinating solutions.